Linguistic construction of the past: Rhetoric in geopolitical conflicts or rhetoric making conflicts? - Valeria E.Chernyavskaya; Safronenkova, Elena L (St. Petersburg State Polytechnical University Journal. Humanities and Social Sciences, 2020)
The paper focuses on the issue of interdependence of ideology and language when representing historical past in political discourse. The past is regarded as an object to be constructed. Linguistic devices are of interest as they construct an evaluative image of the past. We presume that narratives about national history are powerful tools influencing historical understanding and national identity construction. In this study a contribution is made by analyzing specific national historical discourse in the situation of ongoing geopolitical conflict, namely the conflict in the Caucasian region between Armenia and Azerbaijan with regard to the dispute on historical right on the territory of Nagorno-Karabakh. The discourse analytic approach allows to consider texts as parts of social practice. It is applied to a value-based construction of the historical past in texts produced by public figures, including heads of states. The study stresses that through the language of appraisal the past can be presented in a value-based way. Linguistic analysis focuses on evaluative description of the historical past in the frame of certain political interests for the public who are not experts in history.